2023
DOI: 10.1227/ons.0000000000000838
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Robotic-Assisted Digital Exoscope for Resection of Posterior Fossa Tumors in Adults: A Series of 45 Cases

Gabrielle Price,
Alexander Schupper,
Roshini Kalagara
et al.

Abstract: BACKGROUND AND OBJECTIVES: Complete safe resection is the goal when pursuing surgical treatment for posterior fossa (PF) tumors. Efforts have led to the development of the exoscope that delineates tumors from non-neoplastic brain. This investigation aims to assess patient outcomes where PF tumor resection is performed with the exoscope by a retromastoid or suboccipital approach. METHODS: A retrospective analysis was conducted for patients with PF tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Several studies examined the extent of resection attained while using the exoscope and have shown an average extent of resection of up to 95% and a rate of complete resection ranging from 65% to 80% for various brain tumor types [37,[46][47][48][49]. However, it is essential to consider that these figures may vary, and more expansive, rigorously designed studies are needed to assess the exoscope's true impact on the extent of resection, along Recent exoscopes incorporate features such as light filters for 5-aminolevulinic acid (5-ALA), fluorescein, indocyanine green (ICG) video-angiography, and adjustable operative settings [4,40,45].…”
Section: Exoscopementioning
confidence: 99%
“…Several studies examined the extent of resection attained while using the exoscope and have shown an average extent of resection of up to 95% and a rate of complete resection ranging from 65% to 80% for various brain tumor types [37,[46][47][48][49]. However, it is essential to consider that these figures may vary, and more expansive, rigorously designed studies are needed to assess the exoscope's true impact on the extent of resection, along Recent exoscopes incorporate features such as light filters for 5-aminolevulinic acid (5-ALA), fluorescein, indocyanine green (ICG) video-angiography, and adjustable operative settings [4,40,45].…”
Section: Exoscopementioning
confidence: 99%